2012
DOI: 10.1016/j.neuroscience.2012.05.070
|View full text |Cite
|
Sign up to set email alerts
|

The projection and synaptic organisation of NTS afferent connections with presympathetic neurons, GABA and nNOS neurons in the paraventricular nucleus of the hypothalamus

Abstract: Highlights► Ascending NTS fibres target PVN-associated neurons. ► Suggest glutamate as the neurotransmitter. ► Anatomical basis for the different functions of cardiovascular receptors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
70
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(72 citation statements)
references
References 67 publications
2
70
0
Order By: Relevance
“…We presented not only light microscopic, but also fine structural details and synaptology of nNOS-immunopositive septal neuronal elements. Fine structural immunocytochemical studies are rather rare in this field and they deal with other parts of the CNS, such as the spinal cord [43], nucleus of the solitary tract [5], periaqueductal grey matter [7], hypothalamus [1] or visual cortex [29]. Independently of the examined brain area the fine structural characteristics of the nNOS-immunopositive neurons, terminals and dendrites are astonishingly similar to each other as well as to our findings.…”
Section: Discussionsupporting
confidence: 87%
“…We presented not only light microscopic, but also fine structural details and synaptology of nNOS-immunopositive septal neuronal elements. Fine structural immunocytochemical studies are rather rare in this field and they deal with other parts of the CNS, such as the spinal cord [43], nucleus of the solitary tract [5], periaqueductal grey matter [7], hypothalamus [1] or visual cortex [29]. Independently of the examined brain area the fine structural characteristics of the nNOS-immunopositive neurons, terminals and dendrites are astonishingly similar to each other as well as to our findings.…”
Section: Discussionsupporting
confidence: 87%
“…The functional consequences of these distinct stage-dependent responses need to be interpreted through the location and role of these brain-stem nuclei in the blood pressure control circuit. The NTS is known to be the primary site of cardiorespiratory regulatory integration (1,8,9,13,33,46,47). The RVLM receives inhibitory projections from the caudal ventrolateral medulla.…”
Section: Discussionmentioning
confidence: 99%
“…The primers are listed in Supplemental Table S6. 1 Gene expression data analysis. Targets assayed were chosen based on their role in neuromodulation, inflammation, and catecholaminergic regulation from literature and previous unpublished data from this lab.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…PVN presympathetic neurons receive afferent projections from the NTS. 32 NTS neurons innervate GABAergic neurons in the caudal ventrolateral medulla, which, in turn, innervate neurons in the RVLM. 33 It was reported that intracerebroventricular injection of IMD caused a pressor effect and sympathetic activation.…”
Section: Discussionmentioning
confidence: 99%